Strengthening multi-stakeholders platorms in Niger Office zone - Sidibe, M.; Dossou-Yovo, E.R. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report outlines the outcomes of the initial training provided to new multi-stakeholder platforms under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. The training focused on enhancing the capacity of two platforms—Synergie des Exploitants Agricoles de l'Office du Niger (SEXAGON) and the Collective of Women Farmers of the Office du Niger (CFEON)—to disseminate climate-resilient and nature-positive solutions. In total, 40 members of the platforms including 20 males and 20 females were trained on the principles of Climate-Smart Agriculture (CSA), climate change awareness, and effective change management strategies. The report details the objectives, methodologies, and key results of the training, highlighting the need for the platforms to effectively engage in scaling up CSA practices and knowledge within the rice-based systems value chain. Through participatory sessions, platform members were equipped with the skills required to promote climate-adaptive technologies, fostering a more sustainable agricultural landscape in the Office du Niger region.